The psychology of the person - Symington, Neville (Karnac Books, 2012)
This new title, from a distinguished psychoanalyst, will inspire both those in the psychoanalytic field, and the general reader.'In this book I attempt to sketch out a "psychology of the person". The definition of "person" implies that no two people, even identical twins, are the same. Although this is obvious (and no sensible person would quarrel with such a view), yet many terms are used that imply that there is a sameness between two or more people. For instance, it is often said that one individual is identified with another which, in ordinary language, means that he or she makes him or he.